Wideband tunable, high-power, graphene mode-locked ultrafast lasers - Sun,Z; Lin,XC; Popa,D; Yu,HJ; Hasan,T; Torrisi,F; Kelleher,EJR; Zhang,L; Sun,L; Guo,L; Hou,W; Li,JM; et al. (2011)
Ultrafast passively mode-locked lasers with spectral tuning capability and high output power have widespread applications in biomedical research, spectroscopy and telecommunications [1,2]. Currently, the dominant technology is based on semiconductor saturable absorber mirrors (SESAMs) [2,3]. However, these typically have a narrow tuning range, and require complex fabrication and packaging [2,3]. A simple, cost-effective alternative is to use Single Wall Carbon Nanotubes (SWNTs) [4,10] and Graphene [10,14]. Wide-band operation is possible using SWNTs with a wide diameter distribution [5,10]. However, SWNTs not in resonance are not used and may contribute to unwanted insertion losses [10]. The linear dispersion of the Dirac electrons in graphene offers an ideal solution for wideband ultrafast pulse generation [10,15]. © 2011 IEEE.